The rebellion of John against tsar Peter (928) re-discussed - Leszka, Mirosław Jerzy (Balcanica Posnaniensia. Acta et studia, 2017)
The article refers to a repeatedly discussed subject of the rebellion staged by John, the son of Simeon I of Bulgaria, against Peter his (?)step-brother. The author of the study has reanalysed sources on the plot for motives of the conspiracy, its scope, attitude of the Byzantine Empire towards the rebellion and John’s fate after the year 928. The conspiracy has been concluded to have primarily been an aspect of the struggle for power amongst the successors of Simeon. which is not supposed to have been instigated by Byzantium in any way.